Heat transfer and friction characteristics of crimped spiral finned heat exchangers with dehumidification - Nuntaphan A. (2014)
This study experimentally examines the air-side performance of a total of 10 cross flow heat exchangers having crimped spiral configurations under the dehumidification. The effect of tube diameter, fin spacing, fin height, transverse tube pitch, and tube arrangements are examined. The results indicate that the heat transfer coefficient of wet surface is slightly lower than that of dry surface. The effect of tube diameter on the air-side performance is significant. Larger tube diameter not only gives rise to lower heat transfer coefficient but also contributes significantly to the increase of pressure drops. This phenomenon is applicable in both dry and wet condition. For wet surface, the influence of fin height is negligible and the effect of fin spacing on the heat transfer performance is rather small. However, increasing of the fin spacing tends to have a lower heat transfer coefficient. The tube arrangement plays an importance role on the heat transfer coefficient, narrower transverse pitch gives higher heat transfer coefficient. The proposed correlations can predict 75% and 95% of experimental data within 15%. © 2004 Elsevier Ltd. All rights reserved.